The interdependent relationship between the types of investments and income in Republic of Macedonia - Goran Mojanoski; Marko Georgievski; Viktor Mitevski; Viktor Stojkoski (Journal of Contemporary Economic and Business Issues, 2017)
In this paper, we study the interdependent relationship between three types of investments: foreign direct investments, central government investments, and all other investments, and their role in the gross domestic product dynamics in the Republic of Macedonia, by employing the consistent methodology of vector error correction modeling (VECM). Our results reveal that, in the long run, there is only one relationship in which all other investments are dependent variables. In it, the foreign direct investments have a negative effect, thus suggesting the existence of the crowding out phenomena. Additionally, we find that shocks in both foreign direct investments and all other investments have positive, while central government investments have no impact on the gross domestic product. As such, our conclusions can serve policy makers for developing strategies that lead to long run growth.
Keywords: C32; E22; F43; H50; 330; investments; economic growth; crowding out; VECM